2007
DOI: 10.1111/j.1530-0277.2007.00444.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered Gene Expression Profiles in the Frontal Cortex of Cirrhotic Alcoholics

Abstract: These changes in the transcriptome likely contribute to the more severe brain dysfunction in cirrhotic alcoholics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 42 publications
2
67
1
1
Order By: Relevance
“…Although a number of sophisticated in silico approaches have been used to predict the function of nsSNPs on protein structure and activity, the underpinnings for these algorithms are protein sequence alignment (Wang and Moult, 2001), physiochemical differences (Henikoff and Henikoff, 1992), mapping to known protein threedimensional structures (Sunyaev et al, 2001;Stitziel et al, 2003), and combinations thereof (Liu et al, 2007). Different in silico algorithms focus on different aspects of this information, among which the SIFT and PolyPhen algorithms are the main representatives in this field.…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of sophisticated in silico approaches have been used to predict the function of nsSNPs on protein structure and activity, the underpinnings for these algorithms are protein sequence alignment (Wang and Moult, 2001), physiochemical differences (Henikoff and Henikoff, 1992), mapping to known protein threedimensional structures (Sunyaev et al, 2001;Stitziel et al, 2003), and combinations thereof (Liu et al, 2007). Different in silico algorithms focus on different aspects of this information, among which the SIFT and PolyPhen algorithms are the main representatives in this field.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoprecipitation experiments were performed to identify PPIs using synaptic proteins as baits. The following proteins encoded by alcohol-responsive genes were used as baits: syntaxin-1A (Worst et al, 2005), synaptosome-associated protein 25 (Liu et al, 2007), vesicle-associated membrane protein 2 (Worst et al, 2005), dynamin-1 (Saito et al, 2002), and the BK channel (Pietrzykowski et al, 2008). Subsequent immunoblots and mass spectrometric analyses confirmed known and identified novel, interacting protein partners in the co-immunoprecipitates.…”
Section: Interaction Proteomics Approachesmentioning
confidence: 94%
“…Damage to the liver due to long term alcohol misuse results in a higher effective dose reaching the brain, and greater neuropathological damage (Harper, 1998). In addition, the expression profile in the prefrontal cortex of alcohol misusers with cirrhosis of the liver is distinct from those without cirrhosis of the liver (Liu et al, 2007).…”
Section: Case Selectionmentioning
confidence: 99%
“…These include genes involved in protein trafficking, myelination, ubiquitination, apoptosis, cell adhesion, neurogenesis, and neural disease. Studies using whole-genome microarrays (Lewohl et al, 2000;Liu et al, 2004Liu et al, , 2007Liu et al, , 2006Mayfield et al, 2002) and 2-D gel proteomics (Etheridge et al, 2009;Lewohl et al, 2004) have suggested that α-synuclein is differentially regulated in the brain of alcohol misusers relative to controls. A recent study analysing data available from GWAS, animal and human genetic and gene expression studies found the α-synuclein gene (SNCA) to be the top candidate gene for alcoholism (Levey et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation